Reliability Assessment of Offshore Pipeline Due to Pitting Corrosion - Seyed Mohammad Hossein Sharifi; Nima Pirali (International Journal of Maritime Technology, 2020)
Pitting is one of the most localized forms of corrosion attacks which cannot be detected easily. Pitting decreases the pipe wall thickness and also the pipeline strength against environmental and operational loads. The purpose of this article is to investigate the most common reliability methods for estimating the maximum pitting depth and the effect of internal pressure on the remaining strength of corroded pipelines at different times in its lifetime service based on different failure pressure models using first-order approximation and sampling reliability methods. To investigate the effect of pitting growth and variation of internal pressure on pipeline characteristics, sensitivity analysis with gamma index several times in pipeline lifetime was performed. It is concluded that the first-order reliability method was applicable for ASME failure pressure models, also concluding that internal pressure and pipeline wall thickness are the most effective load and capacity parameters in failure probability of corroded pipelines. The reliability analysis was performed for two pipeline classes and two different pipeline wall thicknesses and it is concluded that the increase in pipeline wall thickness has more effect on decreasing the probability of failure (POF) of the pipeline than using a pipeline with higher classification.